LITERASI LEMBAGA KEUANGAN LEASING DI KOTA TASIKMALAYA - Rahmatul Khalik Alwiyasa; Tanti Nurfauziah; Wulan Aftilasyah (Transpublika Publisher, 2022)
The research aims to determine the literacy level of leasing institutions in the people of Tasikmalaya City. The aspects that will be studied in the literacy of leasing institutions include, principles, benefits, products and risks to leasing financial institutions. This research uses quantitative descriptive with survey methods through the distribution of questionnaires online. The object of this study is the people of Tasikmalaya City. Data analysis uses descriptive statistics, then the results of the analysis will be classified using a financial literacy model initiated by Chen & Volpe (1998). The population in this study was the people of Tasikmalaya City with a sample of 180 people using random sampling techniques. The results revealed that the level of financial literacy of Leasing institutions in Tasikmalaya City was 60.04%, which was categorized into a medium level of financial literacy. In detail, the Principle Aspect has the highest score with an average score of 63% which is still classified as medium literacy. Furthermore, the Benefit Aspect and Risk Aspect which have the same value of 61% are also reflected at a medium level of literacy. Meanwhile, the Product Aspect is classified as low by having an average score of 56%.